PANDEMI COVID-19 SEBAGAI PEMODERASI PENGARUH SEKTOR PARIWISATA TERHADAP PENURUNAN PEREKONOMIAN DI PROVINSI BALI - Purba, Samuel Fery; Wahyuningsi, Mentari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
The research objective is to examine and analyze the determinants of the tourism sector (Hotel room occupancy rate (TPKH), Total of domestic and foreign tourist visits (JWDM), and Total of Bali flights (PJB)) that influence Bali's economic growth and to determine the effect of the relationship between these determinants during the COVID-19 pandemic (a moderating factor) in the Province of Bali. A quantitative approach with secondary data from the Bali Province Central Statistics Agency website from January 2017 to December 2021. secondary data from three tourism indicators and COVID-19 as a moderating factor. This study use multiple linear regression to investigate the impact of a variety of related variables. The findings obtained during the analysis were that total of domestic and foreign tourists visits (JWBM) before the COVID-19 pandemic had a positive and significant relationship with Bali's economic growth. The TPKH variable before the COVID-19 pandemic and JWDM during the COVID-19 pandemic had a negative relationship to per capita GRDP in Bali. The JPB variable before the COVID-19 pandemic as well as TPKH and JPB during the COVID-19 pandemic had a negative and insignificant value for Bali's GRDP, which is a proxy for regional economic growth. This condition is due to the COVID-19 pandemic, which has reduced people's mobility; moreover, they have to do PPKM and